Targeting uric acid: a promising intervention against oxidative stress and neuroinflammation in neurodegenerative diseases - Lin Xu; Chengwei Li; Tiantian Wan; Xinyi Sun; Xiaojie Lin; Dong Yan; Jianjun Li; Penghui Wei (Cell Communication and Signaling)
Abstract Oxidative stress and neuroinflammation are recognized as key factors in the development of neurodegenerative diseases, yet effective interventions and biomarkers to address oxidative stress and neuroinflammation in these conditions are limited. Uric acid (UA), traditionally associated with gout, is now gaining prominence as a potential target in neurodegenerative diseases. Soluble UA stands out as one of the most vital antioxidant compounds produced by the human body, accounting for up to 55% of the extracellular capacity to neutralize free radicals. While there is increasing evidence supporting the neuroprotective properties of UA in Parkinson’s disease and Alzheimer’s disease, gaps in knowledge still exist regarding the underlying mechanisms and how to effectively translate these benefits into clinical practice. Moreover, the current UA elevation therapy exhibits unstable antioxidant properties, individual variability, and even adverse effects, limiting its potential clinical applications. This review consolidates recent advancements in understanding how UA exerts neuroprotective effects on neurodegenerative diseases and emphasizes the dual roles of UA in managing oxidative stress and neuroinflammation. Additionally, the review elucidates the mechanisms through which UA confers neuroprotection. Based on this, the review underscores the significance of UA as a potential biomarker and aims to provide a comprehensive understanding of its potential as a therapeutic target, while also addressing possible challenges to clinical implementation.